2018
DOI: 10.3389/fphy.2018.00110
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Dynamics of Individuals in Complex Networks

Abstract: The relation between the behavior of a single element and the global dynamics of its host network is an open problem in the science of complex networks. We demonstrate that for a dynamic network that belongs to the Ising universality class, this problem can be approached analytically through a subordination procedure. The analysis leads to a linear fractional differential equation of motion for the average trajectory of the individual, whose analytic solution for the probability of changing states is a Mittag-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 26 publications
(26 reference statements)
1
24
0
Order By: Relevance
“…However, we use the term "quantum-like coherence" rather than quantum coherence. We note also that Turalska and West [25] used a model of interacting units to mimic a decision making system and found that the behavior of the single units is very well described by Equation (8). This implies that the Caputo fractional derivative may have an important role to play in understanding the conjunction fallacy, that being, given two events A and B the probability P(A) is always greater than the conjoined probability P(A ∪ B).…”
Section: Fractional Diffusion Equationmentioning
confidence: 84%
See 1 more Smart Citation
“…However, we use the term "quantum-like coherence" rather than quantum coherence. We note also that Turalska and West [25] used a model of interacting units to mimic a decision making system and found that the behavior of the single units is very well described by Equation (8). This implies that the Caputo fractional derivative may have an important role to play in understanding the conjunction fallacy, that being, given two events A and B the probability P(A) is always greater than the conjoined probability P(A ∪ B).…”
Section: Fractional Diffusion Equationmentioning
confidence: 84%
“…Further research must be done to confirm these results and to strengthen the foundations for the rigorous theory, which may overlap with research on chaos-assisted tunneling. The Caputo fractional derivatives are manifestations of crucial events, a recent example of the relevance of which to complexity in network dynamics is found in [ 25 ]. In it, Turalska and West studied a social network of interacting individuals at criticality and found that the global complex network generates crucial events.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we follow the discussion of Turalska and West [ 21 ]. The idea of different clocks telling different times arises naturally in physics; the linear transformation of Lorentz in relativistic physics being a familiar example.…”
Section: Introductionmentioning
confidence: 99%
“…If each tick of the discrete clock n is considered to be an event, the relation between operational and chronological time is given by the waiting time PDF of those events in chronological time . Assuming a renewal property for events, as given by a chain condition (convolution) from renewal theory in Section 2.1 , one can relate operational to chronological time [ 21 ]: Every tick of the operational clock is an event, which in the chronological time occurs at time intervals drawn from the renewal waitin -time PDF. This randomness entails the sum over all events and the result is an average over many realizations of the transformation.…”
Section: Introductionmentioning
confidence: 99%
“…The fractional calculus (FC) is a branch of mathematical analysis, which deals with the non-integer integral and derivative operators. The application of the FC has been extensively expanded in different fields of the basic and engineering sciences [2][3][4][5][6][7][8][9]. Over the past few decades, the classical mechanics has been extended by using the new aspects of the FC.…”
Section: Introductionmentioning
confidence: 99%